2020
DOI: 10.1177/1054773820958115
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences for Supportive Care Needs of Women with Breast Cancer-Related Lymphedema: A Phenomenological Study

Abstract: This descriptive phenomenological study was conducted to explore the lived experiences for supportive care needs of women with breast cancer-related lymphedema. Purposive sampling was used to recruit participants. In-depth, semi-structured interviews were conducted to collect data. Thematic analysis method was used for data analysis. Data saturation was achieved after interviewing 19 participants. The study was divided into four main themes and nine subthemes: physical (caused by difficulties in performing hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 35 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…The simplified Chinese version of this scale has been validated in previous study (Li, 2012). Relevant study shown that external support was an important facilitator of lymphoedema selfmanagement (Arikan Dönmez et al, 2021), so the simplified Chinese Medical Outcome Study Social Support Scale was used in this study to test the convergent validity of the LSMBQ. First, the high-low grouping comparison method was used to analyse the discrimination of each item (Wu, 2010).…”
Section: Medical Outcome Study Social Support Scalementioning
confidence: 99%
“…The simplified Chinese version of this scale has been validated in previous study (Li, 2012). Relevant study shown that external support was an important facilitator of lymphoedema selfmanagement (Arikan Dönmez et al, 2021), so the simplified Chinese Medical Outcome Study Social Support Scale was used in this study to test the convergent validity of the LSMBQ. First, the high-low grouping comparison method was used to analyse the discrimination of each item (Wu, 2010).…”
Section: Medical Outcome Study Social Support Scalementioning
confidence: 99%
“…4 Women with BCRL may experience persistent swelling of the arm, hand, breast, and/or chest; feelings of heaviness or fullness; decreased mobility; aching or tingling; and skin tightness or hardening in the affected region. [4][5][6] There is no cure for BCRL; therefore, it requires diligent consistent care to manage the condition. 4 Research on women's experiences with BCRL has been conducted primarily with White non-Latina women in the United States and internationally.…”
mentioning
confidence: 99%
“…9,10,12 To avoid the appearance of having a disability, and to prevent others from staring and asking questions, women may try to hide their compression sleeves or not wear them in public. 5,12 Given the challenge of finding clothes that fit, women also may spend considerable time dressing. 5,6 Some women have reported that BCRL serves as a reminder of their breast cancer diagnosis and treatment, 10 triggering fears of recurrence and worry.…”
mentioning
confidence: 99%
See 2 more Smart Citations